(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2023)
The current era is the information era; people are running on society 5.0, where machines are integrated with humans for a healthy, comfortable, easy, and long life. In general, information is blood, and MIS is body; blood flows for life which can be compared with the flow of information on the organization as per the requirement for decision-making to grow the organization to meet its desired outcome. The overall objective of this research is to assess the effect of MIS on decision-making among academic institutions. This machine can function effectively and efficiently only with the help of data and information for humanitarian assistance for various purposes. Nowadays, every organization cannot run smoothly without the use of MIS. It signifies the dependability of decision-making on MIS. This research has attempted to identify necessary variables. They are used to evaluate the influence of management information systems on decision-support capabilities in the organization. This study also discusses the concept, attributes, characteristics, types of MIS, and the MIS model, and finally, highlights the effect of MIS in decision-making in academic institutions. At the same time, different models and figures are presented to enrich the discussion and to highlight the status of each MIS and DSS information system in an organization’s decision-making process. Here fifteen related articles are incorporated to review the title to ensure the research gap and where conceptual review approach based on descriptive content analysis using long-term classroom discussion. This research will create an awareness to develop an integrated MIS among academic institutions to ensure success through rational scientific decision-making.